Mimarlıkta aks - Akpınar, İpek (Fen Bilimleri Enstitüsü, 1993)
Bu tezde özel bir mimari kurgu olan akslar, öncelikle bir varoluş mekanı oluşturmaları bağlamında tanımlanarak, fiziksel ve kültürel çevreyle etkileşimleri, değişik kültürlerdeki biçimleniş özellikleri ve farklı ölçeklerdeki aksiyal organizasyon yapılan ele alınmıştır. Giriş bölümünde tez konusunun önemi üzerinde durularak, neden bu konunun seçildiği, amaçlanan düşünceler ve araştırmanın çerçevesi ortaya konmuştur. Bu bağlamda izlenecek yol ve tezde yer alacak bölümler hakkında bilgi verilmiştir. Birinci bölümde, mekanın genel bir tamım yapılarak, akslar bir varoluş mekanı olarak ortaya konmuşlardır. Varoluş mekanının yapısı irdelenerek, aksiyal kurgunun bireyin ait oluş, yönleniş ve kimliklenmesindeki rolü tartışılmıştır. İkinci bölümde, çevre fiziksel ve kültürel bir bütün olarak kabul edilerek, aksların bu zengin örüntüde oynadığı rol ele alınmıştır. Kültürel çevre tanımı yapısı ve faktörlerinin üzerinde durularak çevrenin özel bir yer oluşturması irdelenmiştir. Aksiyal kurgunun farklı kültürlerdeki biçimleniş özellikleri semantik açıdan sorgulanmıştır. Üçüncü bölümde, aksiyal mekan organizasyonu herşeyden önce kendisim oluşturan elemanlarla vardır. Aksiyal elemanlar başlangıç, bitiş ve süreklilikleriyle incelenerek oluşturdukları yapılar 'lineer, grid, radyal ve şebeke' olmak üzere dört ana başlık altında toplanmıştır. Aks tipleri ise 'yol, merdiven, köprü, rampa, kule v.b.' özel biçimleniş formları ile aktarılmıştır. Bu aksiyal yapı ve tipler değişen çevre ölçeğinde ortaya koydukları kurgularla ele alınmışlardır. Sonuç bölümünde ise aksın çok özel bir varoluş mekanı yarattığı gerçeğinden hareket edilerek, farklı kültürlerdeki biçimleniş özelliklerinin ışığında bir senteze varılmıştır: bu da aksiyal kurguya gelecekteki tasarımlarda gereken ilgi ve duyarlılığın gösterilmesi gerektiğidir.

The aim of this thesis is to define the axis as a special existential space to display the relationship of this fundamental structure with physical and cultural environment to analyze the features of organization in different cultures and the typology of axial structure. The introduction chapter emphasizes on the significance and the importance of the research area, the purpose and the method of this study. In the first chapter, a conceptual definition of the axis is put forward. General space definitions are explained within a framework that covers its abstract and concrete properties. Space is the idea which man forms and develops as the result of his sense perceptions, mat there exist "things" other than himself and that his own body consists of "parts" and that these bear an orderly relationship to one another which he describes in terms of positions in space and distance from one another. The presence of a body in space not being indepent of time, "a time axis" must be added to the three axes of space dimensions in order to locate it Norberg-Schulz classifies space concept at five levels: -The pragmatic space of physical action, -The perceptual space of immediate orientation, -The existential space which forms man's stable image of his environment, -The cognitive space of the physical world, -The abstract space of pure logical relations. Heidegger is the first who maintains mat existence is spatial: "you cannot divorce man and space ". Space is neither an external object nor an internal experience. Creating arcitectural space means integrating an intended form of life in the place. A place is a qualitative "total" phenomenon which we cannot reduce to any properties. Man's relation to places and through places to spaces consist in dwelling. Dwelling is the essential property of existence. Existential space is a relatively stable system of perceptual schemata or "image" of the environment The field of existential space is represented (concretized) by a corresponding architectural field. Places are the basic elements of existential space: any place contains directions. The vertical direction expresses a rising up or falling down. The vertical has always been considered the sacred dimensions of space. It represent a "path" towards a reality which may be "higher" or "lower" than dairy life. The axis mundi is more than the centre of the world, it represent a connection between the three cosmic realms. The vertical direction also has a more concrete meaning. It expresses man's ability to conquer nature. The tower becomes the symbol of victory and defeat and the vertical column expresses man's power of creation. The horizontal directions represent man's concrete world of action. In a certain sense, all horizontal directions are equal and form a plane of infinite extension. The simplest model of man's existential space is, therefore, a horizontal plane pierced by a vertical axis. But on the plane man chooses and creates paths which give his existential space a more particular structure. Norberg-Schulz analyzes the existential space on several levels as the thing, the furniture, the house, the urban level, the landscape level and the geographical level. These levels are determined by the given environment as well as by man's constitution. The levels of existential space form a structured totality which corresponds to the structure of existence. In things everything is "focused", in nature everything is "contained". And in between there is man's dwelling. Man is a wanderer: as a homo viator, he is always on the way, which implies a possibility of choice. He chooses his place, and hence a certain kind of fellowship with other men. The dialectic of departure and return, of path and goal is the essence of that existential spatiality which is set into work by architecture. An axis / path leads man in direction determined by his purpose and his image of the environment Sometimes the path leads him to a known goal, but often it only indicates an intended direction, gradually dissolving into the unknown distance. Therefore the axis / path represents a basic property of human exis tence, and it is one of the great original symbols. The axis always contains a tension between the known and die unknown. From the beginning of time, man has recognized that to create a place to express the essence of being. Time is not a phenomenon, but the order of phenomenal succesion and change. Primarily life is movement and such it possesses direction and rhytm. The axis / path is therefore a fundamental existential symbol which concretizes the dimension of time. The axis leads to a meaningful goal, where the movement is arrested and time becomes permanent In ancient architecture, we also find a "via sacra" which leads to the centre, and which is used for re-enacting of cosmic events. In the Christian basilica, path (nave), and goal (alter) are unified to symbolize the path of salvation of Christian doctrine. The mobility of man has lead to the creation of paths: these have then- own energy and as such constitute forces. The axis is perhaps the most elementary means of organizing forms and spaces in architecture. It is a line established by two points in space and about which forms and spaces can be arranged in a regular or irregular manner. Although imaginary and not visible, an axis is a powerful, dominating, regulating device. The specific disposition of elements about an axis will determine whether the visual force of an axial organization is subtle or overpowering, loosely structured or formal picturesque or monotonous. In the second chapter, the concept of the cultural environment and the classification of their components are argued. The interrelations between man and environment cause some changes in the physical environment. This changed environment is called "cultural environment". If s a man-made place which visualises, complements and symbolizes man's understanding of his environment A culture is made up, actually of activities of human being: it's a system of interlocking and intersecting actions, a continuous functional pattern. It is intangible and invisible. It has physical ingredents-artefacts; also physical symptoms-the ethnic effects that are stamped on the human face, known as it expression, and the influence of social conditions on the development, posture and movement of the human body. But all such items are fragments mat give the meaning to the total pattern of life only to those who are aquainted with it and may be reminded of it They are ingredients in a culture, not its image. The architect creates his image: he physically presents human environment mat expresses the characteristics rhytmic functional patterns which constitute a culture. As the main function of culture is to produce patterns, the formal characteristics of the environment constitutes the essence of the relationship of the culture with the environment In fact, the environment forms a very special place. And for the formation of the axis in mis place, images, values and symbols imposed by the culture are effective as cultural factors. Every culture has a specific world view: it represents the expectations from life and the way of seeing it. Symbols in a given culture were fixed, known and shared both by the public and the designers. A given element would always or at least in most cases, elicit "the right" responses. The choices are greatly limited by the culture and these limitations are accepted. Traditions which are carried through centuries by the culture have obligatory influences on design, and on architecture. Symbols imply something more than the plain meaning. Symbols of architecture are formed by religion and traditions; and architecture uses forms and materials as symbols. Symbolism is an effective way of explaining things and is used in axis very often: in this chapter axial organizations are reviewed within different cultures. Peoples actions, presuppose an organization of the environment This axial organization consists in abstracting objects from the immediately given phenomena: axis is fixed by means of signs. Thus it becomes a manifestation of meaning in the cultures. Axis creates a symbol-system: it easily adapts itself to regions of the world of objects. This adaptation is possible by means of a common logical form, as path, bridge, tower, etc. Therefore axial symbolization means a represantation of cosmic order in another medium by means of structural similarity such as "mandala11. The meanings of axis creates a relation among cultures: they are based upon the development of symbol-systems which can keep and spread experiences. In the third chapter, axial space organizations are analyzed in the physical environment: its components and characteristics are displayed. The environment is considered as all the conditions, circumstances and influences surrounding, affecting an organism..According to this definition, the environment of man (community) is the physical environment The relation between man and environment causes some changes in the physical environment and this changed environment is called "cultural environment" which can be defined as the "physical effects developed while man is using nature". The analyse of the axial space within the environment is made by means of Elastic Grid which is a systematic exposition of the relationship between aspects of physical environment and other relevant actors. The horizontal axis of the Elastic Grid refers to the scale of the environment from the measure of man alone, through dwellings and neigborhoods, up to ecumenopolis of 30 Million people. The vertical axis consists of types of elements making up nature, man, society, sheels and networks. In this study the horizontal axis of the Elastic Grid is consisted of "building, street, city, areas between cities, country, areas among countries, world and cosmos". The vertical axis consists "sheels, nature and networks which can become elements of the cultural environment. The axis is analyzed by its relations to these elements. Axis as being a strong communication system plays an important role in the organizations of the buildings (shells). Ching defines this organization in five categories such as "central, linear, radial, clustered and grid". Onat adds "enveloping and branched organizations" to these categories. Principally axis and shells are related to each other in three different ways such as: - corridor-street with adjoining buildings, - street along which stand isoleted buildings, - network where paths freely located in park landscapes scattered with freestanding buildings. As Ching says: - axis pass in front of the buildings, - axis pass through the building, - axis terminates or starts in the buildings. As the result axis and buildings (shells) create an interrelationship which help the formation of the cultural environment Man-made places are related to the nature in some basic ways: man wants to make the natural structure more precise. That is, he wants to visualize his "understanding of nature by expressing" the existential foothold he has gained. To achieve this, he builds what he has seen: where nature suggets a delimited space, he builds an enclosure; where nature indicates a direction, he makes a path. While creating these forms, man transforms nature, in a "natural place" which denotes a series of environmental levels, from continents and countries down to the sheltered area under the individual tree. In relation to these environmental levels, landscape plays a distinctive role while serving as the comphrensive stage for everyday life. Thus the spirit of natural place can be classified by means of landscape such as, romantic landscape, cosmic landscape and complex landscape. Axis creates a good reletionship with the natural places by means of geographic conditions which are soil, plant, water and topography. All these elements help the axial organization. But water forms a very special axis system such as Bosphoms, Venice or Bruges. The "how" the extention of the axis primarily depends on the nature of the ground, that is, on the topographical conditions. Topography simply means "place-description"; but it is generally used to denote physical configuration: it can be called the surface relief. With these geographic conditions, axis arranges the nature and the environment becomes a cultural environment As shells and nature, axis creates the same interreletionship with "network". Simonds classifies axial network organization as linear, radial and grid. Ching utilizes his classification for the shells / axis and defines axis / axis relation as "linear, radial, spiral, grid, network and complex". While regarding the examples of axial organization in the historical period, it should be better to make a shorter classification: - one axis which form linear system - two axis which form the rectangular or spherical settlements - more than two axis which form radial and grid. In the city scale, axis realize two basic interrelationship with the squares. The union of axis / axis creates a junction point The union of axis / square can be formed in four basic types. - centrally and at right angles to one side - off-centre and at right angles to one side - meeting a corner at right angles - oblique, at any angle and at any point of entry. After the definition of the axis by means of shells, nature and networks, the axial organization can be analyzed with its elements, scale and functions which form all together the character and the perception properties of the system. The axis can be formed by natural and artificial elements in the type of the path, the stairs, the bridge and the ramp. It can be narrow / wide, long / short relevating to the function, topography, etc. Axis can be used as a pedesterian street, bicycle path, traffic road. Axis are the channels along which the observer customarily, occasionally or potentially moves. As it is seen, they may be streets, walkways, transit lines, canal, railroads. For many people axis, are the predominant elements in their image. People observe city while moving through it, and along these paths the other environmental elements are arranged. Since an axis is essentially a linear condition, it has qualities of direction, and induces movement and views along its path. For its definition, an axis must be terminated at both of its ends: its directional, orderly, dominating. An axis is a unifying element. It may be symmetrical or asymmetric. The approach of the axis to its goal may be frontal, oblique and spiral. These visual aspects of the axis help the perception of the observer. The axial organization is experienced by people passing through it in a definite sequence. Spaces on the axis do not occur in isolation: they are linked together. All spatial sequences should be functional and legible. Sequence of the axis is continuity in the perception and understanding of spaces, and it is achieved by the use of spatial elements to provide succession of visual experiences. As an individual is experiencing axial space by moving through it, that axis is releaved as a chain should lead to the next, without necessarily revealing it. rtit The objective is to excite curiosity as to what lies beyond, and to create drama through the juxtaposition of different types of scenes along the axis. In order to create a sequence along the axis,, the organizational structure may be made by hierarchy, repetition and continuity. Hierarchy is the structure formed by the increasing spaces progressively in size, and hence in importance. The use of repetition may be based on the regular occurrence of open space or of a color, texture or shape. To develop a rhythm, the repetitious sequence must be interspersed at recurring intervals with a contrasting element to create variety. Finally continuity may be used to structure a sequence: it depends on the quality of the transitions between spaces. After studying the cognitive, symbolic and the physical aspects of the axial space, in the fourth chapter "Divanyolu" is chosen as a case study of this thesis. All great cultures have created cultural environments by utilizing or incorporating nature. Divanyolu is one of the most important axis taking a fundamental role in the formation of Istanbul: it is one of the basic element creating genius loci of the city. The history of Divanyolu has started With Istanbul's: mis axis has got active relations since the greek period. During the Roman and Byzantian period, "Mese street" was a unique unifying element at the historical peninsula with its order, colonnade, squares, etc. Ottoman Empire used Divanyolu as the main axis between the old and the new palaces. If we look at the situation of the Divanyolu today, we can see that there is an unplanned development. After the planning activities since 1950's, the visual environment changes day by day. There was not a sufficient and effective master and restoration / conservation plan. The current changes in population and preferences of the actual cultural system deeply affected the Divanyolu axis. The fifth chapter consists of the results of the study. While axis form a very special existential space, it is very important to pay attention to the structure of axial space in architecture and in urban design.
Axis in architecture
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 1993
Keywords: Bina bilgisi; Eksen; Building information; Axis